2014
DOI: 10.4236/jct.2014.56063
|View full text |Cite
|
Sign up to set email alerts
|

Influence of GSTT1, GSTM1 and GSTP1 Polymorphisms on the Development of Breast Cancer

Abstract: Introduction: Every year, more than 10 million women are diagnosed worldwide with breast cancer. Breast cancer remains the leading cause of death from malignancy in women. In Mexico about 12 Mexican women die every day from this disease. Glutathione S-transferase (GST) family consists of a group of isoenzymes involved in Phase II detoxification of xenobiotics by glutathione conjugation. There have been reports showing GST polymorphisms as a risk factor for developing cancer. Objective: Determine if the frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Similar relation was found in tumors with heterozygote genotype of GSTP1 regarding positive and negative IHC PR stain and tumor grade. These results are consistent with studies that showed an inverse correlation with ER (Gilbert et al, 1993;Silvestrini et al, 1997;MoureauZabotto et al, 2006;Rodríguez et al, 2014), and the two studies of Pongtheerat and colleagues which reported GSTP1 polymorphism was unrelated to increased risk of breast cancer, but found an inverse relationship between GSTP1 genotype and progesterone receptor protein (Pongtheerat et al, 2009;Pongtheerat et al, 2011), and positive correlation with better tumor differentiation and grade (Cairns et al, 1992;Haas et al, 2006). The findings of the current study are in harmony with the report of Ge et al who reported that GSTP1 105Val allele carriers were more liable to have a higher histological grade tumor and negative ER stain than Ile/Ile allele carriers (Ge et al, 2013).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Similar relation was found in tumors with heterozygote genotype of GSTP1 regarding positive and negative IHC PR stain and tumor grade. These results are consistent with studies that showed an inverse correlation with ER (Gilbert et al, 1993;Silvestrini et al, 1997;MoureauZabotto et al, 2006;Rodríguez et al, 2014), and the two studies of Pongtheerat and colleagues which reported GSTP1 polymorphism was unrelated to increased risk of breast cancer, but found an inverse relationship between GSTP1 genotype and progesterone receptor protein (Pongtheerat et al, 2009;Pongtheerat et al, 2011), and positive correlation with better tumor differentiation and grade (Cairns et al, 1992;Haas et al, 2006). The findings of the current study are in harmony with the report of Ge et al who reported that GSTP1 105Val allele carriers were more liable to have a higher histological grade tumor and negative ER stain than Ile/Ile allele carriers (Ge et al, 2013).…”
Section: Discussionsupporting
confidence: 82%
“…However, to date the results are still somewhat controversial and may vary from population to population. (Gilbert et al, 1993;Silvestrini et al, 1997;Buser et al, 1997;Helzlsouer et al, 1998;Millikan et al, 2000;Mitrunen et al, 2001;Gudmundsdottir et al, 2001;Huang et al, 2003;Egan et al, 2004;Sreenath et al, 2005;Moureau-Zabotto et al, 2006;Unlu et al, 2008;Saxena et al, 2009;Arun et al, 2010;Pongtheerat et al, 2011;Zhang et al, 2011;Ramalhinho et al, 2011;Aguiar et al, 2012;Ramalhinho et al, 2012;Saxena et al, 2013;Khabaz, 2014;Rodríguez et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As only a part of the HPV infected women develop precancerous cervical lesions or cancer, prophylactic evaluation of GST family enzymes could play a major role in identifying high risk individuals for an efficient therapeutic interference, here including HPV vaccination (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…The GSTP1 gene, a member of the GST Pi class, has approximately 3.2 kb and is found on chromosome 11q13 (Rodríguez et al, 2014). GSTP1 is involved in cell protection through the apoptotic process, and its polymorphic forms do not synthesize essential proteins that bind to enzymes present in the JNK pathway (De Luca et al, 2012).…”
Section: Introductionmentioning
confidence: 99%